2020
DOI: 10.1002/advs.201902656
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interface Energy Band Alignment Optimization and Defect Passivation toward Efficient and Simple‐Structured Perovskite Solar Cell

Abstract: Efficient electron transport layer–free perovskite solar cells (ETL‐free PSCs) with cost‐effective and simplified design can greatly promote the large area flexible application of PSCs. However, the absence of ETL usually leads to the mismatched indium tin oxide (ITO)/perovskite interface energy levels, which limits charge transfer and collection, and results in severe energy loss and poor device performance. To address this, a polar nonconjugated small‐molecule modifier is introduced to lower the work functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 38 publications
1
77
0
Order By: Relevance
“…Numerous research outcomes have demonstrated that the energy band alignment and interfacial charge recombination between the ETL and perovskite layer exert a significant impact on the device performance. [ 4–7 ] Therefore, it is pre‐requisite to develop an ETL with tailored morphology, optoelectronic properties, and compatible band alignment with perovskite, in order to fabricate high performance PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research outcomes have demonstrated that the energy band alignment and interfacial charge recombination between the ETL and perovskite layer exert a significant impact on the device performance. [ 4–7 ] Therefore, it is pre‐requisite to develop an ETL with tailored morphology, optoelectronic properties, and compatible band alignment with perovskite, in order to fabricate high performance PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Other fascinating optoelectronic properties of these magic perovskite materials, for example, ambipolar charge transport capability, low exciton dissociation energy and long charge diffusion length, point to the great potential for constructing high‐performance, ETL‐free PSCs, which is thought to be a perfect solution to address the dilemma of balancing high efficiency and low production cost [12] . Owing to continuous research efforts to optimize the materials, interfaces, device structures and fabrication processes, the power conversion efficiencies (PCEs) of state‐of‐the‐art ETL‐free PSCs already exceed 20 %, which is approaching the certified PCE as high as 25.2 % for their ETL‐containing counterpart [13–19] . The next step is to further reduce the efficiency gap between the ETL‐free “simplified” PSCs and devices with standard architecture, but this is still a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…To simplify the device structure of PSCs, HTL‐free and ETL‐free PSC devices have come onto the horizon of researchers . The photovoltaic performance of ETL‐free PSCs can be improved by utilizing perovskite films with large‐sized perovskite crystals or adding extra PbI 2 into the perovskite precursor solution .…”
Section: Introductionmentioning
confidence: 99%